Diversity and intraspecific variation of floral volatile compounds underscoring the terpenoids and methyl esters among the wild Clematis species and their cultivars - Yifan Jiang; Xiaohua Ma; Wanbo Zhang; Qingdi Hu; Jian Zheng; Renjuan Qian (Ornamental Plant Research, 2023)
Floral scent is a crucial characteristic that greatly affects the reproductive process and also the market value of numerous ornamental crops. As the pivotal species in basal dicotyledonous, Clematis is widely favored as an ornamental vine plant due to its varied colors and shapes of flowers. However, the diversity and complexity of the floral fragrance in Clematis is largely unexplored. Thus, on the basis of the initial sensory survey, four fragrant wild Clematis species and five cultivars were selected to investigate the variation of the floral volatile profiling between the wild Clematis species and their cultivars. Our results demonstrated that a total of 162 volatile compositions, including terpenoids, benzenoids, fatty acid derivatives, and N-containing compounds, were successively detected by the combination of dynamic headspace collection and GC-MS analysis. The qualitative and quantitative comparison combined with clustering and PCA analysis indicated the interspecific discrepancy in floral volatiles between the wild Clematis species and cultivars. C. finetiana exhibited a higher emission with the characteristic releasing pattern being distinct from other species. In conclusion, the exploitation of the emission patterns, biosynthesis, and potential biological functions of floral scent, especially for terpenoids and methyl esters, provides a comprehensive understanding of volatile metabolism in fragrant Clematis species and their cultivars. These findings can be useful for aromatic resources screening and breeding strategies developing to create new aromatic cultivars of Clematis.